Parasite development and host responses during the establishment of Trypanosoma brucei infection transmitted by tsetse fly - Barry, J.D.; Emery, J.L. (Cambridge University Press, 1984)
Following inoculation ofTrypanosoma bruceiinto large mammals by the tsetse fly a local skin reaction, the ‘chancre’, develops due to trypanosome proliferation. We have cannulated the afferent and efferent lymphatics of the draining lymph node in goats and examined the onset of a cellular reaction, the emigration of the parasite from the chancre and the development of both antigenic variation and the specific immune response. The chancre first became detectable by day 3 post-infection, peaked by day 6 and then subsided. Lymphocyte output increased 6- to 8-fold by day 10 and the number of lymphoblasts increased 50-fold in this period. Both then declined. Trypanosomes were detected in lymph 1–2 days before the chancre, peaked by days 5–6, declined during development of the chancre and then peaked again. The bloodstream population appeared by days 4–5 and displayed different kinetics from that in lymph. Recirculation of parasites through the lymphatics ensued. Lymph-borne trypanosome populations were highly pleomorphic. Parasites in lymph expressed firstly a mixture of the Variable Antigen Types (VATs) which are found characteristically in the tsetse fly, this being followed by a mixture of other VATs. The two groups overlapped in appearance. In the bloodstream the same sequence of events occurred although 2 or 3 days later. The specific antibody response, as measured by radioimmunoassay and agglutination, arose within a few days of the first detection of each VAT. Activities appeared first in the lymph and then in plasma.